Notopterol Attenuates Monocrotaline-Induced Pulmonary Arterial Hypertension in Rat - Huang, Lin; Li, Huayang; Huang, Suiqing; Wang, Shunjun; Liu, Quan; Luo, Li; Gan, Shuangjiao; Fu, Guangguo; Zou, PeiYun; Chen, Guangxian; Wu, Zhongkai (Frontiers in Cardiovascular Medicine, 2022)
Introduction: Current targeted pulmonary arterial hypertension (PAH) therapies have improved lung hemodynamics, cardiac function, and quality of life, however, none of these have reversed the ongoing remodeling of blood vessels. Considering notopterol had shown the antiproliferative and anti-inflammatory properties in previous studies, we hypothesized that it could play a role in ameliorating PAH. Methods: In vivo, we conducted monocrotaline (MCT) induced PAH rats and treated them with notopterol for 3 weeks. Then the rats were examined by echocardiography and RV catheterization. The heart and lung specimens were harvested for the detection of gross examination, histological examination and expression of inflammatory molecules. In vitro, human pulmonary arterial smooth muscle cells (HPASMCs) were treated with notopterol after hypoxia, then cell proliferation was assessed by cell counting kit-8 and Edu assay, and cell migration was detected by wound healing assays. Results: We found that notopterol improved mortality rate and RV function while reduces right ventricular systolic pressure in MCT-induced PAH rats. Furthermore, notopterol reduced right ventricular hypertrophy and fibrosis, and it also eased pulmonary vascular remodeling and MCT induced muscularization. In addition, notopterol attenuated the pro-inflammatory factor (IL-1β, IL-6) and PCNA in the lungs of PAH rats. For the cultured HPASMCs subjected to hypoxia, we found that notopterol can inhibit the proliferation and migration of HPASMCs. Conclusion: Our studies show that notopterol exerts anti-inflammatory and anti-proliferative effects in the pulmonary arteries, which may contribute to prevention of PAH.